Digestibilidade do amido e disponibilidade de ca e p em alimentos energéticos extrusados para a tilápia do nilo (Oreochromis niloticus) - Guimarães, Igo Gomes; Pezzato, Luiz Edivaldo [UNESP]; Barros, Margarida Maria [UNESP]; Tachibana, Leonardo; Fernades, Rosangela do Nascimento [UNESP] (FapUNIFESP (SciELO), 2011)
Apparent digestibility coefficients (ADC) of starch and calcium (Ca) and phosphorus (P) apparent availability were evaluated in five cereal grain products and byproducts (corn, wheat meal, rice grain, rice bran and sorghum) for Nile tilapia. Chromic oxide was used as an external digestibility marker. The highest Ca and P apparent availability, respectively, were obtained for rice grain (43.03 and 64.79%), sorghum (39.89 and 58.09%) and corn (22.18 and 19.48%), while rice bran (-31.49 and 3.25%) and wheat meal (5.80 and 1.18%) showed the lowest values. Starch digestibility varied between 99.45 and 95.59% among the evaluated ingredients. This high ADC of starch observed in this study confirms that Nile tilapia is able to efficiently digest and utilize complex carbohydrates.

O coeficiente de digestibilidade aparente (CDA) do amido e a disponibilidade aparente do cálcio (Ca) e fósforo (P) de cinco alimentos energéticos (milho, farelo de trigo, quirera de arroz, farelo de arroz e sorgo) foram avaliados para a tilápia do Nilo. O óxido de crômio-III foi utilizado como indicador inerte das rações. Apresentaram os maiores CDA do Ca e P, respectivamente, a quirera de arroz (43,03 e 64,79%), o sorgo (39,89 e 58,09%) e o milho (22,18 e 19,48%), enquanto o farelo de arroz (-31,49 e 3,25%) e o farelo de trigo (5,80 e 1,18%) apresentaram os menores valores. A digestibilidade do amido apresentou-se entre 99,45 e 95,59% entre os alimentos energéticos avaliados. O alto CDA do amido observado neste estudo confirma a grande capacidade da tilápia do Nilo de utilizar carboidratos nas formas mais complexas.
Starch digestibility and ca and p availability in cereal grain products and by-products in extruded diets for nile tilapia (Oreochromis niloticus)
Keywords: ADC; Carbohydrates; Extrusion; Mineral; Carboidratos; CDA; Extrusão; Minerais; Tilápia